Nuevos registros de placas columnares de crinoideos (Echinodermata, Crinoidea) del Paleozoico Superi - Esquivel-macías, Carlos; Solís-marín, Francisco; Estela Buitrón-sánchez, Blanca (Coloquios de Paleontología, 2004)
We report eighteen new records of crinoids from Mexico represented by columnar plates found in the Patlanoaya, Olinalá/Los Arcos and Del Monte formations. All the records belong to the Late Paleozoic (Mississippian, Pennsylvanian and Permian) from reef facies dated with fusulinids, brachiopods and ammonoids. The fossils considered here were collected in 1995 when field work was more intense. The new records include two new morphotypes (may be new species). Because of these collects we have increased the number of fossil crinoids described from Mexico since 1993 from 15 to 33 species, and those described from the Late Paleozoic, from 11 (in 1993) to 29 species. This increase enhance the use of crinoids in dating and correlate the rock units in the area. We evaluate the possibilities of the study of Late Paleozoic crinoids from Mexico, based on the richness and variety of species found. We discuss the importance of such richness for the environmental reconstruction. We propose the continuity of the Ouchita paleobasin to southern Mexico based on crinoids records. We discuss the validity of using crinoids columnar plates parataxonomy, because of the lack of Mexicans calyx elements on which traditional taxonomy is based.